Ways to avoid chromaticity shift on touch screens - Galvan, Glenn (Knovel, 2012)
As more visual displays are being fitted with touch screen technology their human factor performance can be affected adversely. Integrating the two technologies can introduce challenges for system designers and integrators. This article discusses some of the challenges in integrating the two technologies and discuss an anomaly known as chromaticity shift.
Keywords: Touch screens.; Information display systems.; Human-computer interaction.; elektronické knihy; electronic books